RELIGIOUS TOLERANCE IN INDONESIA: AN INCREASINGLY LARGE SPACE - Mahfudin Setiawan, Agus; Sananta, Rachma Dyah Auliya; Nurlaeli, Fiki (Universitas Islam Negeri Raden Intan Lampung, 2023)
In the middle of an advanced civilization, these people face a threat to their unity in the form of dark shadows. Theological excuses are often used to justify conflicts, with religion being portrayed as a main factor. However, the village of Sidoasri in Malang district serves as a foundation for practicing tolerance. Indonesia is known worldwide for its diversity in religion, culture, ethnicity, language, and customs. These noble values need to be safeguarded through mutual tolerance and respect.In the democratic realm of Indonesia, maintaining harmony among religious communities and society is the responsibility of all parties involved. Cooperation between the public and the government is crucial in preserving religious harmony, providing services, regulating affairs, and empowering the community. Research indicates that strong religious tolerance is developed through a lengthy process that follows conflicts. Dogmatic religious beliefs are not conducive to fostering tolerance. Various factors such as social conflicts, culture, politics, and the economy contribute to the different forms of religious tolerance.